Implementation of Building Information Modelling for Road Rehabilitation and Reconstruction Project: Liquefaction Disaster of Palu Area - Andri Irfan Rifai; Hikmawati Thalib; Muhamad Isradi; Joewono Prasetijo (IJEBD (International Journal of Entrepreneurship and Business Development), 2022)
Purpose: Utilization of Building Information Modeling (BIM) is believed to improve planning accuracy, mitigate construction risks, and better plan the entire life cycle of infrastructure asset projects. The application of BIM technology in post-disaster management can combine GIS technology (Geographic Information System) with BIM technology itself, or commonly referred to as geospatial BIM. The purpose of this paper is to apply BIM technology, explain the stages of road planning and modeling with BIM, and identify the advantages of using BIM compared to conventional methods. The road planning location is the location of the Jono Oge liquefaction disaster, Palu, Indonesia. Design/methodology/approach: Data collection, data processing with Agisoft Metashape, DEM data input, and orthophoto image data processed by Agisoft Metashape to Autodesk® InfraWorks®, road planning with Autodesk® InfraWorks®, road planning model output and field data presentation. 3D models, IMX format files, FGDB format files, and animation videos. Findings: The application of BIM technology in planning and modeling road projects at liquefaction locations can be made using Agisoft Metashape software to process aerial photo data taken using drones and using Autodesk® InfraWorks® software for planning and modeling of the road. Research limitations/implications: Modeling Road design in the application of BIM and the use of Autodesk® InfraWorks® applications on the project. We are not modeling the pavement, just visualizing the geometry of the road. Practical implications: BIM implementation can drive time, effort, and realistic 3D visualization. Originality/value: Original paper Paper type: A case study